In situ consolidation of carbon fiber PAEK via laser-assisted automated fiber placement. (15th January 2023) - Heathman, Nathaniel; Koirala, Pratik; Yap, Timothy; Emami, Anahita; Tehrani, Mehran
Abstract: Automated fiber placement (AFP) of thermosetting composites has been one of the leading manufacturing techniques for aerospace structures over the last decade. Thermoplastic composites (TPCs) offer several advantages including a high toughness, recyclability, weldability, and potential for rapid out-of-autoclave manufacturing. High-power heating sources and flexible compaction rollers can be used to melt and consolidate TPC tapes via AFP to form large structures in a layer-by-layer manner as used in additive manufacturing. This paper investigates the in-situ consolidation AFP of TPC tapes (ICAT) toward their process optimization and revealing mechanisms that govern the ICAT process. To this end, a laser-assisted AFP system was utilized to fabricate short beam strength samples from carbon fiber reinforced low-melt polyaryletherketone (LM-PAEK™) at various processing parameters. Analysis of results revealed how ICAT process parameters affect interlaminar bonding, crystallinity, and void content in manufactured parts. Multiphysics finite element analysis (FEA) was also carried out to reveal mechanisms that control void, crystallinity, and bonding in ICAT. Finally, a comparison of post-fracture specimens made via ICAT with traditional compression molding was used to explain the underlying failure mechanisms in ICAT coupons. This study shows that at AFP rates of up to 0.15 m/s, high interlaminar shear strengths, up to 60 MPa, are possible to achieve with low void content (<1%) and high crystallinity (>20%), proving that ICAT is potentially a viable process for manufacturing the next generation of aerospace composites.